Perancangan Front end Aplikasi Penjualan Berbasis Web Menggunakan Metode HCD - Indah Rafiqa Zulva; Edi Susilo; Muhammad Fazlie (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
KUD Jaya Makmur is a cooperative located in Kampung Kumbara Utama. The business fields of this KUD are convenience stores (Waserda), production facilities (Saprodi), and Savings and Loan Units (USP). The waserda business sector records sales transactions using the iPos application version 4.0.5.3. created with Visual Basic .NET. The iPos application version 4.0.5.3 used in KUD Jaya Makmur found several problems. Waserda has a server and 3 cashiers, but the application is only used on the server and 1 cashier, so the other cashiers manually write down goods sales. There are also problems with the stock count feature. Any number written in the stock table will still be displayed as zero. This causes the difference between incoming and outgoing goods to not match. Some of these problems have become obstacles faced so far. This research was conducted to design a web-based sales application front end using the HCD method. Front end testing was carried out using Standard ISO 25010 in terms of UX. Through UX testing conducted on the KUD Jaya Makmur sales application and the iPos version 4.0.5.3 application in the same way, it was found that the sales application for KUD Jaya Makmur was better in all aspects.